2013
DOI: 10.1093/ntr/ntt189
|View full text |Cite
|
Sign up to set email alerts
|

Brief Exposure to Secondhand Smoke Reversibly Impairs Endothelial Vasodilatory Function

Abstract: We sought to determine the effects of brief exposures to low concentrations of tobacco secondhand smoke (SHS) on arterial flow-mediated dilation (FMD, a nitric oxide-dependent measure of vascular endothelial function) in a controlled animal model never before exposed to smoke. In humans, SHS exposure for 30 min impairs FMD. It is important to gain a better understanding of the acute effects of exposure to SHS at low concentrations and for brief periods of time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
32
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 21 publications
4
32
1
1
Order By: Relevance
“…21,22 This rat model showed that impairment of FMD occurred with one minute of exposure to cigarette SHS. 23 We report here that brief exposure to little cigar SHS impairs vascular function in rats as least as much as exposure to cigarette SHS.…”
mentioning
confidence: 68%
“…21,22 This rat model showed that impairment of FMD occurred with one minute of exposure to cigarette SHS. 23 We report here that brief exposure to little cigar SHS impairs vascular function in rats as least as much as exposure to cigarette SHS.…”
mentioning
confidence: 68%
“…Two of the subjects were tobacco users and while they abstained 12 h before FMD testing, constituents of cigarette smoke may contribute to endothelial dysfunction and the precise mechanisms by which tobacco leads to this altered vascular reactivity remain unclear, thus a longer period of abstinence may have been necessary [48, 49]. Additionally, we did not assess whether there was secondhand smoke exposure [50]. The heterogeneity of SSc treatment may have influenced the FMD results.…”
Section: Discussionmentioning
confidence: 99%
“…Like all particulate air pollution, 16 smoking and exposure to secondhand smoke both lead to impairment of endothelial function in humans as measured by arterial flow-mediated dilation 17 (FMD), an effect that occurs in a few minutes in humans [18][19][20] and rats. 21 Reflecting these rapid effects, implementation of comprehensive smokefree laws are followed by drops in heart attacks and other conditions. 3, p. 435-443, 22,23 As one would expect based on this evidence, FMD drops in rats after one minute of marijuana sidestream smoke, with impairment lasting at least 90 minutes (longer than for tobacco smoke), independent of the presence or absence of cannabinoids.…”
mentioning
confidence: 99%